Fundamentals of Human Resource MANAGEMENT - Noe, Raymond A.; Hollenbeck, John R.; Gerhart, Barry; Wright, Patrick M. (McGraw-Hill, 2024)
Fundamentals of Human Resource Management 2024 Release provides a complete, concise introduction to human resource management for the general business manager who wants to learn more about how HRM is used in the everyday work environment. Its adaptive learning program and its engaging, focused, and applied content make it the fastest growing HRM program on the market. The authors have won numerous prestigious teaching and research awards. This, along with their teamwork and consulting experience, delivers a learning program strong in depth and breadth, and current in research and practice simply not found in other products.